(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The subject of the study is as follows: The increasing number of accidents during this time period resulted in the creation of numerous difficulties, including mental diseases and their personal and social effects. As a result, the researcher decided to develop Light Contact Boxing exercises and assess their influence on the physical and psychological components of anxiety and depression in the treatment of certain mental patients in the province of Babylon. The study’s goals were to: - -Prepare Light Contact activities for mental patients suffering from phobias and despair. The researcher employed the experimental strategy: The researcher was chosen from two equal groups for the experimental approach. (an experimental group and a control group with a pre and post-test). The sample size is (26) boxers, and (13) boxers were chosen at random. The sample was separated into two groups (experimental and control) and ranged in age from 20 to 25 years. The researcher then presented, examined, and discussed the findings: It showed the arithmetic mean and standard deviations and the data were put into tables, where the researcher utilized the statistical package (SPSS) and then examined and discussed the results in an accurate scientific manner. The most important conclusions: Based on the findings of this investigation, the researcher came to the following conclusions: 1- The light-contact technique exercises utilized on mental patients had an effect on the development of physical variables. 2- The light-contact technique exercises utilized on mental patients had an effect on the development of fear and depression characteristics. The following were the most important recommendations: 1- Paying close attention to the weekly evaluation of pulse variables in all exercise strains and determining the time for rest and effort on this basis. 2- Taking care of and focusing on the mechanical mechanism of executing physical and skilled activities. 3- Emphasizing training variety, such as weights, flexibility, and others. 4- Concentrating on other talents in various kinds with aerobic exercises. 6- Instructing patients to conduct exercises in sports with limited areas and open skills, such as swimming, volleyball, and martial arts training with shadow boxing or mild contact.